Advancing gender equality in the construction sector through public procurement: Making effective use of responsive regulation. (November 2020) - Wright, Tessa; Conley, Hazel
Labour market segregation continues to be a major barrier to gender equality, with the construction industry an example of a particularly male-dominated sector. Drawing on evidence from the Women into Construction project, established to increase women's opportunities to work on the construction of London's Olympic Park, the article argues that public procurement is a potentially powerful tool for breaking down gender segregation. This is particularly effective when new forms of responsive and reflexive legislation require private sector contractors to achieve social objectives. The authors argue that this could be made more effective through greater powers of engagement for stakeholders, including trade unions.